Zonning, Circulation And Convenience Of Traditional Market In Bandar Lampung. (Case Study Way Kandis Traditional Market) - Negho D E E; Munawaroh A S (International Conference on Engineering and Technology Development (ICETD), 2017)
The traditional market is a shopping tool to make ends meet. Circulation conditions and zoning traditional market is still not good enough so that still need to beimproved in order to increase user convenience market. This study aims to determine the zoning in Market Way Kandis, knowing the condition of circulation in Market Way Kandis,determine the level of user comfort Market Way Kandis circulation and circulation planning and zoning arrangement model of good to overcome the problems in Market WayKandis. The research method is descriptive. Research approach to the study of literature and case studies. Study of literature on the theory of the circulation of the traditionalmarkets and traditional markets zoning theory. The case study by dividing the data into two, namely primary data and secondary data. Analysis of the data by comparing thestandards based Neufert and Panero, as well as other literature, describe the results of a questionnaire and find solutions to the circulation and zoning better market. Based on theresults of this study concluded that circulation and zoning arrangement in the traditional market is very influential on the market user convenience in their daily activities. From thediscussion, it was found that there are still many elements of good circulation and zoning in Market Way Kandis that do not meet the criteria set standard. According to traders accessto the market, loading and unloading goods, and parked the vehicle in the market that includes easy with an average ratio of 65% on Market Way Kandis. That's because they aredoing the activity when the market is quiet. Meanwhile, according to the buyer at Market Way Kandis comfort level of circulation in the market is quite good with an average ratioof 63% of respondents answered easily. To overcome the problems of circulation and zoning in Market Way Kandis should be redesigned so that the circulation in the marketand zoning that is in these markets that can meet the existing standards.